Stressors and depressive disorders in rheumatic diseases - Tatyana Andreyevna Lisitsyna; D Yu Veltishchev; E L Nasonov (Научно-практическая ревматология, 2013)
The paper discusses the common comorbidity of immune inflammatory rheumatic diseases (RD) and depression. It considers the causes and mechanisms, which are common to these diseases, namely, the provocative role of chronic psychosocial stress; neuroendocrine dysregulations of an immune response, which give rise to the hyperproduction of the proinflammatory cytokines determining the magnitude of the major clinical syndromes of RD and depression — chronic pain, fatigue, sleep disorders, functional insufficiency. The impact of depression on patient treatment adherence and efficiency and the course and outcome of RD is discussed. Particular attention is given to the timely therapy of depression in RD, to the effect of genetically engineered biological agents on depressive symptomatology, to the need for a personified approach to prescribing antidepressants. By taking into account the importance of detection and treatment of depressive disorders in rheumatologic practice from the clinical standpoint and in terms of medical, social, and economic consequences, the author propose an interdisciplinary approach to managing the patients with RD with the participation of rheumatologists, psychiatrists, neurologists, and medical psychologists.